Design of a Website-Based Arabic Typing Application for Students of Arabic Language Education Program at University - Nasiha, Wardatun; Afifah, Nor; Amir, Ahmad Nabil (CV. Bimbingan Belajar Assyfa, 2023)
Today's internet technology has advanced extremely quickly and is still expanding. The virtual world is a place where everyone and any group of individuals are free to engage in their activities. In this all-IT era, typing skills are very important for students. Because almost all student activities are carried out by typing such as compiling papers, reports, theses and others. However, the results of observations made at the Arabic Language Education Study Program at the University of Muhammadiyah Malang show that the skills of typing Arabic texts for Arabic Language Education Study Program students are still minimal. The aim of the research is to design a website-based Arabic Typing application and test the feasibility of using the application. The research subjects were students of the Arabic Language Education Study Program. The development model used is the ADDIE model. Through research and development, researchers are tasked with designing applicationsArabic Typingwebsite-based and test the feasibility of using the application for Arabic Language Education Study Program students. Based on media expert validation obtained an average percentage of eligibility of 97.11% (Very Feasible), whereas based on material expert validation obtained an average percentage of eligibility of 85% (Very Feasible). The results of the feasibility test by students obtained an average percentage of eligibility of 83.9% (Very Feasible). On this basis the Arabic Typing application based on this website is very feasible to use as a medium to improve Arabic text Keyboarding skills specifically for students of Arabic Language Education Study Program Faculty of Islamic Stadies at University of Muhammadiyah Malang